2009
DOI: 10.1186/1741-7007-7-23
|View full text |Cite
|
Sign up to set email alerts
|

Noisy splicing, more than expression regulation, explains why some exons are subject to nonsense-mediated mRNA decay

Abstract: Background: Nonsense-mediated decay is a mechanism that degrades mRNAs with a premature termination codon. That some exons have premature termination codons at fixation is paradoxical: why make a transcript if it is only to be destroyed? One model supposes that splicing is inherently noisy and spurious transcripts are common. The evolution of a premature termination codon in a regularly made unwanted transcript can be a means to prevent costly translation. Alternatively, nonsense-mediated decay can be regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 76 publications
(132 reference statements)
4
63
1
Order By: Relevance
“…While it is difficult to quantitatively assess the expression of such proteins, multiple studies have demonstrated that alternatively spliced mRNAs accumulate with NMD inhibition (6)(7)(8)10). Although the physiological/pathological inhibition of NMD occurs with eIF2␣ is phosphorylation, a condition that blunts translation, we have demonstrated that many mRNAs stabilized with NMD inhibition are still actively translated despite eIF2␣ phosphorylation, including functional proteins and maladaptive peptides (3,5).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…While it is difficult to quantitatively assess the expression of such proteins, multiple studies have demonstrated that alternatively spliced mRNAs accumulate with NMD inhibition (6)(7)(8)10). Although the physiological/pathological inhibition of NMD occurs with eIF2␣ is phosphorylation, a condition that blunts translation, we have demonstrated that many mRNAs stabilized with NMD inhibition are still actively translated despite eIF2␣ phosphorylation, including functional proteins and maladaptive peptides (3,5).…”
Section: Discussionmentioning
confidence: 88%
“…However, the full biological consequences of NMD regulation are unknown. These consequences include the stabilization of mutated and alternatively spliced transcripts which could encode deleterious dominant negative, truncated, and/or misfolded proteins (6)(7)(8)(9)(10). The recognition that NMD is dynamically regulated raises the question of how the cell adapts to these aberrant proteins when NMD is physiologically or pathologically inhibited.…”
mentioning
confidence: 99%
“…Thus, the regulation of unproductive splicing of SR protein transcripts is proposed to play a role in the auto-regulation or homeostatic control of these splicing regulators. 18 Consistent with this, Zhang et al 13 examined human and mouse orthologues of well annotated protein coding genes for PTC containing transcript isoforms and determined that only the small fraction (2%) that exhibited strong evolutionary conservation of the PTC containing transcript isoforms were likely to represent bona fide examples of regulated unproductive splicing coupled to NMD. These observations suggest that the portions of the gene directly influencing production of the PTC containing isoform are under purifying selection and will remain conserved between organisms with conserved PTC containing splice isoforms, assuming that the mechanisms of alternative splice determination and PTC recognition were also conserved.…”
Section: W Brad Barbazukmentioning
confidence: 81%
“…13 While many PTC containing transcript isoforms may result from imprecise splicing, there remain several examples of genes that are truly regulated by coupling PTC containing alternatively spliced transcript isoforms with NMD. The majority of these encode components of the ribosome 14,15 and splicing machinery.…”
Section: W Brad Barbazukmentioning
confidence: 99%
“…Nonsense mediated decay (NMD) is a molecular surveillance mechanism that selectively degrades aberrant transcripts produced as a result of nonsense or splice-site variants [234][235][236]. NMD of aberrant transcripts should result in extreme allelic ratios (close to zero or one).…”
Section: Majority Of Aberrant Alleles Do Not Affect Expression Severelymentioning
confidence: 99%